Thermodynamics and An Introduction to Thermostatistics [2nd ed.] - Callen, Herbert B. (New York: Wiley, 2007)
It is the only text to cover both thermodynamic and statistical mechanics--allowing students to fully master thermodynamics at the macroscopic level. Presents essential ideas on critical phenomena developed over the last decade in simple, qualitative terms. This new edition maintains the simple structure of the first and puts new emphasis on pedagogical considerations. Thermo statistics is incorporated into the text without eclipsing macroscopic thermodynamics, and is integrated into the conceptual framework of physical theory.
Keywords: Thermal physics; Thermodynamics; Statistical Mechanics